Eccentrically Loaded Slip-Resistant Connections - Kulak, Goeffrey L. (Engineering Journal, 1975)
Although eccentrically loaded connections should be avoided whenever possible, designers are frequently faced with situations where this type of joint must be used. Such cases could be the provision of crane girder brackets or beam web splices (Figs. 1a and 1b). Eccentricity is present even in a standard beam connection (Fig. 1c), although the effect of the eccentricity is usually not significant. Considerable attention has been directed in recent years toward the assessment of the ultimate strength of eccentrically loaded connections, whether welded or fastened with high-strength bolts. One situation which has received very little attention, however, is the eccentrically loaded bolted connection in which slip is undesirable and friction-type high-strength bolts are employed. As far as is known, no tests except those which will be reported in this presentation have been conducted on this type of connection. The purpose of this report is to review the procedure recommended for the design of slip-resistant eccentrically loaded bolted connections and to compare the results obtained in this fashion with the available experimental data.